Surrogate-based design optimization of a centrifugal pump impeller. Issue 8 (3rd August 2022) - Jaiswal, Ashutosh Kumar; Siddique, Md. Hamid; Paul, Akshoy Ranjan; Samad, Abdus
Abstract : The input power to a centrifugal pump is optimized by changing the impeller blade exit angle. In the optimization, blade exit angles of three meridional profile layers are selected as the design variables, while pump shaft power and head developed are the multi-objective optimization functions obtained through a surrogate model. A multi-objective genetic algorithm is used to find the optimum design point. Computational fluid dynamics simulations are performed to solve Reynolds-averaged Navier–Stokes equations using a shear-stress transport turbulence model for the closure term. Manipulation of the impeller blade angle profile affects both shaft power and efficiency without affecting the head at the best efficiency point, corresponding to a mass flow rate of 1.75 kg/s. The optimum design point of the pump impeller shows an enhancement (>10%) in pump efficiency. Improved flow separation near the trailing edge of the impeller blade and uniform blade loading decreases the input power required at the shaft of the pump impeller.